Application of genefishing discovery system on differential gene expression study for prokaryotic system - Chua, Kek Heng; Chai, H.C.; Puthucheary, Savithri Devi (Academic Journals, 2010)
GeneFishing Discovery is a system applied on disease and gene related research for eukaryotes and the starting material for the study could be either total RNA or mRNA. In this study we demonstrate the use of this discovery system for a prokaryotic system by modifying the eukaryotic protocol using the poly (A)-tailing approach. As an example we compared the gene expression pattern of two closely related species of bacteria under the same family (Burkholderia thailandensis and Burkholderia cepacia) with satisfactory results.